Propriedades tribomecânicas de superfícies de titânio carbonitretadas por plasma - Rocha, Ricardo Cesar da Silva (2012)
Interstitial compounds of titanium have been mainly studied due to the large range of properties acquired when C, N, O and H atoms are added. In this work, surfaces of TiCxNy were produced by thermochemical treatments assisted by plasma with different proportions of Ar + N2 + CH4 gas mixture. The Ar gas flow was fixed in 4 sccm, varying only N2 and CH4 gas flows. During the thermochemical treatment, the plasma was monitored by Optical Emission Spectroscopy (OES) for the investigation of the influence of active species. After treatments, C and N concentration profile, crystalline and amorphous phases were analyzed by Nuclear Reaction (NRA). Besides tribomechanical properties of the Ti surface were studied through the nanohardness measurements and friction coefficient determination. The worn areas were evaluated by profilometry and Scanning Electronic Microscope (SEM) in order to verify the wear mechanism present in each material. It has been seen which the properties like nanohardness and friction coefficient have strong relation with luminous intensity of species of the plasma, suggesting a using of this characteristic as a parameter of process